Heissophila macrotheleae Schuh, 2006, the first record of the subfamily Heissophilinae from China (Hemiptera: Heteroptera: Plokiophilidae) - Yin, Jia-Dong; Bu, Wen-Jun; Xie, Qiang (Zootaxa, 2023)
Heissophila Schuh, 2006, a monotypic genus of Heissophilinae (Hemiptera: Plokiophilidae), is newly recorded from Oriental China based on Heissophila macrotheleae Schuh, 2006 collected from Yunnan Province, China. The diagnosis of the species is expanded based on the newly collected materials. In addition, a DNA barcode of H. macrotheleae and host spider are provided. Photographs of the co-existing web-loving bugs and the natural habitat are also present.